Europes crisis without end: The consequences of neoliberalism run amok - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2013)
This paper argues the euro zone crisis is the product of a toxic neoliberal economic policy cocktail. The mixing of that cocktail traces all the way back to the early 1980s when Europe embraced the neoliberal economic model that undermined the income and demand generation process via wage stagnation and widened income inequality. Stagnation was serially postponed by a number of developments, including the stimulus from German re-unification and the low interest rate convergence produced by creation of the euro. The latter prompted a ten year credit and asset price bubble that created fictitious prosperity. Postponing stagnation in this fashion has had costs because it worsened the ultimate stagnation by creating large build-ups of debt. Additionally, the creation of the euro ensconced a flawed monetary system that fosters public debt crisis and the political economy of fiscal austerity. Lastly, during this period of postponement, Germany sought to avoid stagnation via export-led growth based on wage repression. That has created an internal balance of payments problem within the euro zone that is a further impediment to resolving the crisis. There is a way out of the crisis. It requires replacing the neoliberal economic model with a structural Keynesian model; remaking the European Central Bank so that it acts as government banker; having Germany replace its export-led growth wage suppression model with a domestic demand-led growth model; and creating a pan-European model of wage and fiscal policy coordination that blocks race to the bottom tendencies within Europe. Countries, particularly Germany, can implement some of this agenda on their own. However, much of the agenda must be implemented collectively, which makes change enormously difficult. Moreover, the war of ideas in favor of such reforms has yet to be won. Consequently, both politics and the ruling intellectual climate make success unlikely and augur a troubled future.
urn:nbn:de:101:1-201403118187
Keywords: E00; E24; 330; Financial crisis; euro zone; neoliberalism; Finanzkrise; Wirtschaftsliberalismus; Eurozone